Chile : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Chile's economic performance was very strong during most of the 1990s, but the country suffered a recession in 1998-99. In early 1998, Chile faced a widening external current account deficit-resulting from surging domestic demand and a large drop in copper export prices-which together with turbulence in world financial markets weakened investor confidence and put downward pressure on the currency. Chile has maintained a very open trade regime and has continued with the unilateral phased reduction of its uniform external tariff rate.